TOPOLOGY OPTIMIZATION DESIGN OF RELIABILITY STRATEGY FOR TENT FRAME BASED ON UNCERTAINTY THEORY - LI KongWei; XU BaoLiang; LUO Yi; LV GuiFang (Jixie qiangdu)
Guided by the uncertainty theory, this paper considers the complex and variable working conditions of tents and expounds the feasibility of finite element analysis under the condition of uncertainty of both material and working conditions. It then proposes the topology optimization based on reliability. The scheme takes the reliability index as the constraint condition and transforms uncertain parameters into deterministic parameters, and then the variable density algorithm topology optimization is performed. Taking two typical structure frames of military and civil tents as examples, respectively, the stress of the frame under wind load is considered, and the feasibility of the design scheme and algorithm logic is verified. The results of the mechanical simulations show that the scheme not only obtains the ideal results, but also avoids repeated iterative scheme trial calculations, thus significantly reducing the time costs and workload of the R＆D process, thus promising optimal promotion value and applicability in the engineering fields.